Financial literacy and spending habits of UiTM students / Nurhafizah Ahmad ... [et al.] - Ahmad, Nurhafizah; Alias, Fadzilawani Astifar; Mahlan, Siti Balqis; Hamat, Muniroh; Shamsuddin, Maisurah (Unit Penerbitan JSKM, 2024)
Interest in examining personal finance issues, particularly money management, has surged in recent years as society recognizes its significance. Proficiency in money management is a crucial aspect of preparing students for a quality life as working adults, given that their spending habits during their university years can significantly impact their financial behavior in the future. Reviewing existing literature from research conducted outside of Malaysia underscores the necessity for financial literacy among students to preempt potential challenges arising from a lack of knowledge in individual financial management. This study underscores the pivotal role of financial literacy among students by delving into their background, family income and spending habits. The research utilizes data gathered from questionnaires, analyzed using SPSS version 26.0. The correlation coefficient of 0.697 between financial literacy and spending habits for university students shows a strong positive relationship, meaning that when students know more about finances, they tend to spend money more wisely. This highlights the need for universities to teach students about managing money effectively to help them make better financial decisions.